An Islamic and Statutory Comparison on the Protection of Labor Rights: Toward an Progresif Legal Framework - Halim, Patimah; Jumardin, Marlina Aulia; Satriani, Indra (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The main problem in this research is how to compare the protection of workers in fiqh muamalah and labor law. From the main problem, sub-problems are formulated, namely how the concept of work in Islam, how the protection of workers’ rights in Islam and how the protection of workers’ rights in the law. This research is literature (librari research) which examines several literature studies both journals and books related to labor. Working in the context of Islam is an obligation in terms of maintaining life. In fiqh muamalah, there are several protections of workers’ rights, namely the right to receive a salary, the right to receive wages and the right to obtain job security. While in the context of legislation is the social and technical protection of labor, as well as social security protection.